A public sector accounting technology and its association with a transition to responsible government. (4th May 2017) - Baker, Ron; Rennie, Morina D.
ABSTRACT: This study examines the introduction of an accounting technology in the Province of Canada, namely the collection and reporting of all revenues and expenditures from departments and customs offices. Drawing on insights from Foucault's discontinuities in systems of thought, governmentality, and discipline, we argue that while this technology was not an incontrovertibly superior approach, it was consistent with a new rhetoric associated with the transition from colonial sovereign rule to responsible government.